Effect of Preoperative Education on Anxiety and Stability of Vital Signs of Preoperative Patients in Siti Rahmah Padang Hospital - Heru Purnomo (CV. Get Press Indonesia, 2026)
Stable vital signs are essential indicators of surgical readiness, yet many patients experience preoperative anxiety that can negatively affect these physiological parameters. This study aimed to determine the effectiveness of preoperative education in improving vital sign stability before surgery. A quasi-experimental pretest posttest design was conducted involving 20 surgical patients at Siti Rahmah Padang Hospital. Systolic and diastolic blood pressure, heart rate, respiratory rate, and anxiety levels were measured before and after structured preoperative education. Paired t-tests were used for data analysis.The results showed significant improvements in vital signs following the intervention. Systolic blood pressure decreased from 135 mmHg to 120 mmHg (p = 0.002), diastolic pressure from 85 mmHg to 80 mmHg (p = 0.002), heart rate from 90 bpm to 75 bpm (p = 0.015), and respiratory rate from 22 to 18 breaths/min (p = 0.004). Anxiety scores also declined substantially, from 18 to 12 (p = 0.001).In conclusion, preoperative education effectively stabilizes vital signs and reduces anxiety, supporting better physical and psychological readiness for surgery. Integrating structured education into routine preoperative care is strongly recommended to enhance overall surgical preparedness and patient outcomes.